Strategies to mitigate dissociative and psychotomimetic effects of ketamine in the treatment of major depressive episodes: a narrative review. (18th August 2017) - Cooper, Matthew D.; Rosenblat, Joshua D.; Cha, Danielle S.; Lee, Yena; Kakar, Ron; McIntyre, Roger S.
Abstract: Objectives Replicated evidence has demonstrated that ketamine exerts rapid-acting and potent antidepressant effects. Notwithstanding, its promise to mitigate depressive symptoms and suicidality in antidepressant-resistant populations, several limitations and safety concerns accompany ketamine including, but not limited to, the potential for abuse and psychotomimetic/dissociative experiences. The focus of the current narrative review is to synthesise available evidence of strategies that may mitigate and fully prevent treatment-emergent psychotomimetic and dissociative effects associated with ketamine administration.Methods PubMed, Google Scholar and ClinicalTrials.gov were searched for relevant articles.Results Potential avenues investigated to minimise psychotomimetic effects associated with ketamine administration include the following: (1) altering dosing and infusion rates; (2) route of administration; (3) enantiomer choice; (4) co-administration with mood stabilisers of antipsychotics; and (5) use of alternative N -methyl-d -aspartate (NMDA)-modulating agents. Emerging evidence indicates that dissociative experiences can be significantly mitigated by using an intranasal route of administration, lower dosages, or use of alternative NMDA-modulating agents, namely lanicemine (AZD6765) and GLYX-13.Conclusions Currently, intranasal administration presents as the most promising strategy to mitigate dissociative and psychotomimetic effects; however, studies of strategies to mitigate the adverse events of ketamine are limited in number and quality and thus further investigation is still needed.